How can we resocialize adolescents in rehabilitation schools in Malaysia? Islamic education and programs as an alternative approach - Noor Insyiraah Abu Bakar, Mohd Muslim Md Zalli, Zahari Suppian, Azlina Abu Bakar @ Mohd, Faridah Hanim Yahya (Tanjung Malim, 2024)
How can we resocialize adolescents in rehabilitation schools in Malaysia? Islamic education and programs as an alternative approach by Noor Insyiraah Abu Bakar, Mohd Muslim Md Zalli, Zahari Suppian, Azlina Abu Bakar @ Mohd, Faridah Hanim Yahya